PERILAKU ETIS BAWAHAN: Perlukah Seorang Pemimpin Menjadi Etis, Otentik dan Adil Disaat Bersamaan? - Sigit Puspito; Amir Fikri; Kurnia Endah Riana (Halu Oleo University, 2023)
The ethical standard of government workers is higher than the ethical standard of society in general. The behavior of government workers can have implications and get the public attention. This study aimed to analyze the direct and indirect effect of ethical leadership, authentic leadership, and organizational justice on follower ethical behavior of Dinas Pekerjaan Umum Penataan Ruang dan Perumahan Rakyat Provinsi Kalimantan Timur government workers. Quantitative research was conducted involving data from 99 government workers through online questionnaires. The data were then analyzed using the PLS-SEM analyses to test the hypothesis. The results showed that ethical leadership had a positive effect on followers’ ethical behavior and organizational justice. Meanwhile, organizational justice did not have a significant effect on followers’ ethical behavior. Authentic leadership moderates the relationship between ethical leadership and follower ethical behavior